Sweet's syndrome associated with systemic lupus erythematosus: A case report and review of the literature. Issue 8 (20th May 2013) - Tsuji, Hideaki; Yoshifuji, Hajime; Nakashima, Ran; Imura, Yoshitaka; Yukawa, Naoichiro; Ohmura, Koichiro; Miyagawa‐Hayashino, Aya; Kabashima, Kenji; Mimori, Tsuneyo
Abstract: A 35‐year‐old Japanese female patient with systemic lupus erythematosus (SLE) presented with fever, erythematous papules and nodules, and polyarthralgia. Skin biopsy of a nodule was compatible with Sweet's syndrome. The papules/nodules were well treated with an oral glucocorticoid. Thirty cases of Sweet's syndrome associated with lupus erythematosus (LE) have been reported in the published work. The mean age was 34.2 years. They showed a higher male ratio (male : female, 1:2) compared with patients with SLE (1:9) and Sweet's syndrome (1:3.7). Sweet's syndrome may occur as a manifestation of LE, and a moderate dose of an oral glucocorticoid will result in a good response.